2016
DOI: 10.1080/14789450.2016.1203783
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of Aspergillus fumigatus – clinical implications

Abstract: The traits that make A. fumigatus a successful colonizer and pathogen of humans are multi-factorial. Thus, a global investigative approach is required to elucidate the mechanisms utilized by the fungus to cause disease. Expert commentary: In doing so, a better understanding of disease pathology can be achieved with improved therapeutic/diagnostic solutions, thereby improving patient outcome. Proteomic analysis permits such investigations and recent work has yielded insight into these mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 130 publications
(201 reference statements)
0
7
0
Order By: Relevance
“…Annotation is complicated in that A. fumigatus is rich in protein families which have different functions in spite of similar sequences and in that the redundancy of certain gene families requires multiple deletions to assess a relevant phenotype (e.g., chitin synthase gene family) (165,166). Transcriptome (167)(168)(169)(170) and proteome (171)(172)(173)(174)(175) databases are becoming available and will be used to compare omics data obtained under different conditions. It should be noted that the genetic background of the parental strain is important and may complicate the omics studies, since parental fungal strains may differ in virulence (176).…”
Section: Tools and Strategies To Study The Pathobiology Of A Fumigatmentioning
confidence: 99%
“…Annotation is complicated in that A. fumigatus is rich in protein families which have different functions in spite of similar sequences and in that the redundancy of certain gene families requires multiple deletions to assess a relevant phenotype (e.g., chitin synthase gene family) (165,166). Transcriptome (167)(168)(169)(170) and proteome (171)(172)(173)(174)(175) databases are becoming available and will be used to compare omics data obtained under different conditions. It should be noted that the genetic background of the parental strain is important and may complicate the omics studies, since parental fungal strains may differ in virulence (176).…”
Section: Tools and Strategies To Study The Pathobiology Of A Fumigatmentioning
confidence: 99%
“…Enolase (Aspf 22) has been reported an allergen which stimulates a strong IFNγ immune response in humans and its homolog in C. albicans showed partial protection as a vaccine candidate (Denikus et al 2005 ; Chaudhary et al 2010 ). Presence of enolase (involved in energy metabolism) in hyphae of Aspergilli suggests that this enzyme may facilitate tissue invasion in the host (Denikus et al 2005 ; Moloney et al 2016 ; Shankar et al 2018 ). In A. fumigatus , enolase was abundantly expressed under the influence of antifungal drug suggesting energy metabolism is vital to overcoming the drug stress.…”
Section: Proteomic Approach To Characterise the Antifungal Response Imentioning
confidence: 99%
“…Previous studies on A. fumigatus using 2-DE and MALDI-TOF showed higher expression of protein that function in metabolism, protein biosynthesis, transport, and translation initiation factors in germinating conidia as compared to hyphae (Vödisch et al, 2009 ; Kubitschek-Barreira et al, 2013 ). Proteins from primary metabolism such as enolase/Aspf22 and glyceraldehyde 3-phosphate dehydrogenase were observed on hyphal surface suggesting that these proteins act as adhesion molecules against host (Denikus et al, 2005 ; Moloney et al, 2016 ). Using 2D-DIGE approach, it has been observed that proteins involved in secondary biosynthetic pathways and proteins biosynthesis were over expressed in germinating conidia, while in hyphae, most abundant proteins expressed were from metabolic processes (Kubitschek-Barreira et al, 2013 ).…”
Section: Determinants To Exit Conidial Dormancymentioning
confidence: 99%